Pembuatan Biodiesel Dari Minyak Biji Nyamplung Dengan Sintesis Katalis Basa Na2SiO3/Fe3O4 - Bahar, Helmi; Saputra, Edy; Zultiniar, Zultiniar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Biodiesel is an alternative energy to replace fossil fuels. It can be synthesized by transesterification process of palm oils. Commonly the process of producing biodiesel was used NaOH or KOH as homogeneous catalyst which has the disadvantage because the formation of side products such as soaps and complexity of the separation of catalyst. This research aims to derive biodiesel from seed calophyllum inophyllum oil (CIO) through transesterification using heterogeneous base catalyst Na2SiO3/Fe3O4. Catalyst Na2SiO3/Fe3O4 was synthesized from fly ash palm oil, sodium hydroxide, and iron powder. Condition operation the transesterification are molar ratio of oil:methanol 1:9 and loading catalyst 3%-w with under stirring 300 rpm. The highest yield of biodiesel is 89,48% under the transesterification reaction temperature 60 oC, reaction time 2 hours. Density (40°C) of biodiesel is 862,56 kg/m3, kinematic viscosity (40°C) is 3,54 mm2/s, flash point is 140°C and acid value is 0,50 mg-KOH/g-biodiesel.Keyword: Biodiesel, Esterification, Catalyst, seed calophyllum inophyllum oil (CIO) and Transesterification.